Magnetic properties of crystalline mesoporous Zn-substituted copper ferrite synthesized under nanoconfinement in silica matrix - Najmoddin, Najmeh; Beitollahi, Ali; Devlin, Eamonn; Kavas, Hüseyin; Mohseni, Seyed Majid; Åkerman, Johan; Niarchos, Dimitris; Rezaie, Hamidreza; Muhammed, Mamoun; Toprak, Muhammet S. (Microporous and mesoporous materials, 2014)
[Display omitted] •We fabricated a multicomponent mesoporous product by a novel nanocasting route.•The proposed method provides a high phase purity and large specific surface area.•We studied the effect of nanoconfinement on the magnetic properties of the final product.•Enhancement of saturation magnetization of the material under nanoconfinement.•We propose a model for spin configuration in the sublattices of the material. A series of ordered mesoporous single phase Cu1−xZnxFe2O4 spinel ferrites, with x ranging from 0.00 to 0.75 with a step increment of 0.25, are prepared by a novel nanocasting route with the aid of vinyl-functionalized mesoporous silica as a hard template. All samples display a relatively high surface area and narrow pore size distribution from nitrogen sorption analysis. The magnetic hysteresis loops of these samples measured at 300K, the temperature dependence of the zero field cooled (ZFC) and field cooled (FC) magnetization curves and the Mössbauer Spectra show the presence of superparamagnetic nanoparticles in all samples. The hysteresis data indicate that the maximum saturation magnetization of 52 emug−1 is obtained for the composition with x=0.25. For x⩾0.5, the saturation magnetization decreases as a result of the cation redistribution within tetrahedral (A) and octahedral (B) sites which weakens the A–B interactions due to triangular Yafet–Kittel spin arrangement on the B-sublattice. The observed magnetic features are attributed to the confined spaces of the host material which acts as a nanoreactor, limiting the growth of the embedded oxide phase and significantly influencing the cation distribution of copper–zinc ferrite on the A and B sites.